Implementation of Writing Process Approach - Furaidah Furaidah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
This study aimed at describing the implementation of Writing Process Approach in an informal classroom of fourth and fifth graders of Barrington Elementary School in Columbus, United States. The data were gathered from five-week observation. The results showed that (1) students were provided with regular, abundant opportunity to write, (2) students were free to choose their own topics with the general theme that the teacher set, (3) there were student-student conferences, student-teacher conferences, and whole-class conferences which allowed the teacher and also the peer to scaffold students in their meaning-making process, (4) language was taught out of students’ individual and whole class writing contexts, (5) students were surrounded by rich literature, (6) the implementation of the writing process did not follow a linear predetermined, rigid stages, but was based on students’ individual characteristics.